PENGARUH LIVE STREAMING (MELIPUTI : INTERAKSI, WAKTU NYATA DAN ALAT PROMOSI) SHOPEE TERHADAP KEPUTUSAN PEMBELIAN DI KONTER RADJA CELL BOJONG GEDE KABUPATEN BOGOR - Tika Kartika Asri; Syaiful Anwar; Mujito; Adinda Nurul Ikhsani (Economicus : Jurnal Ekonomi dan Manajemen, 2025)
This study aims to determine the effect of Shopee Live Streaming (including interaction, real-time, and promotional tools) on purchasing decisions at the Radja Cell Counter in Bojonggede, Bogor Regency. The results of this study indicate that all variables, namely interaction, real time, and promotional tools simultaneously have a positive and significant influence on purchasing decisions with Fcount> Ftable (18.796> 2.14) with a significance level of 0.001 <0.10. Then the results of the hypothesis test show that the real time variable has a significant and significant influence on purchasing decisions with a Tcount value of 4.645> Ttable value of 1.660 with a significance value of 0.001 <0.10. Then the promotional tool variable has a significant and significant influence on purchasing decisions with a Tcount value of 2.736> Ttable value of 1.660 with a significance value of 0.007 <0.10. And finally, the interaction variable does not have a significant influence on purchasing decisions with a Tcount value of 1.080 <Ttable value of 1.660 with a significance of 0.283 <0.10. Based on this study, the most dominant or most influential variable is the Real Time variable. This can be seen in the results of multiple linear regression analysis where the Real Time variable has the largest coefficient, namely 1.419.